Addressing the challenges and constraints of social protection policies for Peruvian women domestic workers: the ANITA project study protocol - Maria Lazo-Porras; Maria Kathia Cardenas; Nathaly Aya Pastrana; Christopher Meaney; Andrew David Pinto; Archna Gupta; María Sofía Cuba-Fuentes; Silvana Perez-Leon; Janeth Tenorio-Mucha; Sebastián García; Jill Portocarrero; Karina Romero Rivero; et al. (BMJ Open)
Introduction Domestic workers (DWs) are vulnerable to precarious or informal working conditions with limited access to social protection policies such as employer-paid health insurance or retirement pensions. This study aims to examine the working conditions, health status and access to healthcare for women DWs in Peru and propose recommendations to improve their access to social protection policies.Methods and analysis The project uses a participatory action research approach by engaging three committees: a DW co-researcher committee, an advisory committee and a steering committee. The first two include former or current DWs, while the third includes policymakers and academics. We use a sequential mixed-methods design organised in four phases: (1) secondary data analysis (n=4216): using two Peruvian national surveys to characterise working conditions, health status and access to healthcare; (2) face-to-face survey (n=448): with DWs in three cities, using respondent-driven sampling to further characterise working and health conditions and to identify factors that influence knowledge of and access to social protection policies; (3) qualitative interviews (n=30–46): with DWs, leaders of DW organisations, employers and policymakers to gather different perspectives on the facilitators and barriers to access to social protection policies; and (4) deliberative dialogues (n=14–26): with DW, leaders of DW organisations, employers, policymakers and academics to identify key barriers to the implementation of social protection policies and to develop recommendations for overcoming these barriers.Ethics and dissemination Phase 1 and Phase 2 received ethical clearance from Universidad Peruana Cayetano Heredia in Peru and Unity Health Toronto in Canada. Phase 3 and Phase 4 received ethical clearance from PRISMA Charitable Association in Peru and Unity Health Toronto in Canada. To mobilise knowledge, in collaboration with the committees, we will co-generate policy briefs and audiovisual materials to disseminate the results from this project to different audiences and sectors.